Kétoldalú nemzetközi szerződés alkalmazásának felfüggesztése fegyveres konfliktus miatt - Szalai, Anikó (Debreceni Jogi Műhely, 2020)
The effect of armed conflict on bilateral international treaties of the belligerent parties has undergone a considerable change in the past century. From the concept of termination as the effect of armed conflict by the time of World War II practice of the States had reached the position of suspension of application or no effect at all. This question is regulated solely under customary international law, but the practice of states and doctrine is not readily available and sometimes may be contradictory.Suspension in the case of armed conflict considerably differs from the rules set out in the 1969 Vienna Convention on the Law of Treaties. The lengthy procedure which is based on the negotiation of the parties of the relevant bilateral treaty is almost impossible in the circumstances of an armed conflict, especially with respect to the hostile relationship between the parties.When dealing with this issue one finds that in the practice of States non-application of treaties during an armed conflict exists, however from the viewpoint of principles of international law, namely the principles of pacta sunt servanda, good faith, ex injuria jus non oritur and rule of law this practice - to say the least - is questionable.